Survey on Physical Fitness for the Men's Volleyball Team at SMP Negeri 12 Kaur - Handis Hergo; Supriyanto Supriyanto; Azizatul Banat (Sinar Sport Journal, 2022)
The purpose of this study was to describe the physical fitness of the men's volleyball team at SMP Negeri 12 Kaur. This research will use survey method and descriptive type with quantitative approach. The population in this study was the volleyball team of SMP Negeri 12 Kaur consisting of 15 male volleyball athletes. And then it will be used as a research sample, because it takes all members of the population. The data collection technique used a test survey. The data analysis technique used is descriptive statistical technique, the data analysis used in this study uses descriptive quantitative analysis techniques with percentages. Based on the results of the study, it was known that the physical fitness of the men's volleyball team at SMP Negeri 12 Kaur. Based on the results of the analysis, it shows that the physical fitness of the men's volleyball team at SMP Negeri 12 Kaur is in the very good category. The results of the classification of the data for the physical fitness of students above can be seen that of the 15 students who took the test, it showed that the physical fitness students were in a very good classification, 8 students or 53.33%, both 3 students or 20% and enough 4 people or 26, 66%. So it can be concluded that most of the students already have very good physical fitness...